Liver transplants for noncitizens/nonresidents: What is the problem, and what should be done?. Issue 11 (30th August 2018) - Rahmel, Axel; Feng, Sandy
Abstract : This editorial examines controversial issues raised by Ferrante and Goldberg (page 2663 ) as they revisit waitlistings and transplants for noncitizens/nonresidents and identify a high prevalence of lost‐to‐follow‐up in this population.